2001
DOI: 10.1590/s0074-02762001000400013
|View full text |Cite
|
Sign up to set email alerts
|

TT virus infection in children and adults who visited a general hospital in the south of Brazil for routine procedure

Abstract: TT virus (TTV) is a newly described nonenveloped human virus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
(14 reference statements)
0
9
0
2
Order By: Relevance
“…Despite its large spectrum, it has been shown that the Takahashi assay [2000b] is not able to amplify TTV DNAs from all positive samples [Biagini et al, 2000b;Vasconcelos et al, 2001], indicating the necessity to perform several PCR assays to assess the true TTV prevalence in a determined population . Thus, it cannot be excluded that some sera tested negative for TTV were in reality TTV positive.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its large spectrum, it has been shown that the Takahashi assay [2000b] is not able to amplify TTV DNAs from all positive samples [Biagini et al, 2000b;Vasconcelos et al, 2001], indicating the necessity to perform several PCR assays to assess the true TTV prevalence in a determined population . Thus, it cannot be excluded that some sera tested negative for TTV were in reality TTV positive.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred fifty-two (83%) samples had been tested previously for TTV DNA by using three different PCR assays [Takahashi et al, 1998;Tanaka et al, 1998;Leary et al, 1999], and 68 (45%) positive by at least one PCR assay [Vasconcelos et al, 2001].…”
Section: Blood Samplesmentioning
confidence: 99%
“…The different sequences derived from the same patient could be very close genetically or very separated (percent nucleotide difference from 0.5% to more than 30%). Sequences derived from Most, but not all, serum samples have been tested previously for TTV DNA [Vasconcelos et al, 2001]. …”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Concomitantly with the progressive characterization of Anellovirus genus members, the improvement of TTV PCR assays, which were initially unable to detect a wide range of genotypes, has led to increasing measurements of TTV prevalence in various populations (6,19,20). Much progress in TTV detection has been done since then, with the use of primers located in a short, highly conserved genomic region (15,21,22).…”
Section: Discussionmentioning
confidence: 99%